Penerapan AISAS Dan Guerilla Strategy Terhadap Keberhasilan E-commerce Pertanian - Akbar, Bintang Mukhammad Burhanudin (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2019)
The development of technology, which is increasingly fast, provides distortion to many sectors of the business. At present, all areas inevitably use technology as part of business acceleration. Agricultural e-commerce is one of the firms that is currently developing and trying to be an alternative in providing agricultural product needs. The approach used in the study is AISAS and partial least square. The results of the survey that companies need to improve sharing behavior and apply the effects of guerilla marketing better.